Therapeutic effects of Eucommia ulmoides extract on osteoporosis rat models: a systematic review and meta-analysis - Chen, Zhen; Leng, Chuan; Rui, Tang; Feng, Chaoqun; Li, Tong; Yu, Yang; Zhong, Lei; Fan, Xiaohong (Frontiers in Pharmacology, 2025)
BackgroundEucommia ulmoides Oliv. Is a plant in the family Eucommiaceae and genus Eucommia. For thousands of years, it has been one of the most frequently used botanical medicines. Recent research has highlighted the therapeutic effects of its extracts for osteoporosis. However, its benefits still need to be thoroughly analyzed.ObjectiveThis study aimed to systematically evaluate the efficacy of Eucommia ulmoides extract in osteoporotic rat models and explore its underlying mechanisms.MethodsFollowing the PRISMA guidelines, a comprehensive literature search was conducted across PubMed, Web of Science, Embase, and four other databases. A total of 511 records were identified, and 18 randomized controlled trials (RCTs) were ultimately included. The risk of bias in the included studies was assessed using the SYRCLE tool. Data synthesis and statistical analyses were performed using Stata SE 18 and RevMan 5.4 software.ResultsE. ulmoides extract significantly improved bone mineral density (SMD = 2.44, 95% CI 1.83–3.05, p < 0.000001), trabecular number (MD = 0.87, 95% CI 0.59–1.15, p < 0.000001), trabecular thickness (MD = 0.02, 95% CI 0.01–0.03, p < 0.000001), and bone volume fraction (SMD = 2.82, 95% CI 1.76–3.88, p < 0.000001), while reducing trabecular separation and structural model index. Serum estradiol levels increased significantly, while tartrate-resistant acid phosphatase and osteocalcin levels decreased. Sensitivity analysis confirmed the robustness of the findings, with no significant publication bias detected.ConclusionE. ulmoides extract is an effective treatment for osteoporosis. It promotes bone formation, inhibits bone resorption, and improves bone microarchitecture. These findings support its potential as a plant-derived therapeutic agent for osteoporosis.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD420251003546.